Habsburg on the Throne of England. The Position of Philip Habsburg in England from 1554 to 1558 - Makówka, Magdalena (Vade Nobiscum, tom XX/2019: Studia z historii politycznej i wojskowej, 2019)
The wedding of Philip of Spain and Mary I of England was a cause of a major controversy. There was a fearthat the Queen’s marriage with the Habsburg could possibly be a reason for many threats to the English independence. In this case the highly specific provisions regarding the Philip’s power concluded during the marriage are not surprising. While him being in England, Philip was displaying an interest in the English domestic policy and was actively participating in the administering of the country. Moreover, his actions leaded to England taking part in the war with France resulting in losing of Calais by the Philip’s wife homeland. Childless death of the Queen was the reason why the Habsburg had lost all of his English influences.